SGLT2 INHIBITORS DECREASE CARDIOVASCULAR DEATH AND HEART FAILURE HOSPITALIZATIONS: A SYSTEMATIC REVIEW - Iqbal Anand, Muhammad; Prayuda, Chrisan Bimo; Phillo, Patrick; Nathan, Daniel Setiawan; Maulidya, Tara Titian; Widanarti, Endah Tri; Akmilia, Vera; Amelia, Devita Nur; Pramasari, Alifa Puspita; Suprapto, Agus (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
According to the World Health Organization (WHO), cardiovascular disease is the leading cause of death from noncommunicable diseases (NCDs). It is responsible for 17.5 million deaths, which accounts for 46% of all deaths caused by noncommunicable diseases. Additionally, 80% of these deaths occur in low-middle income countries, and it is anticipated that this number will rise to 23.6 million in 2030. SGLT2 inhibitors are currently indicated as first- or second-line therapies of type 2 diabetes mellitus (T2DM) in patients who have established cardiovascular disease, high or very high cardiovascular risk, renal illness, or heart failure. This is the case in both Europe and the United States of America. In individuals who already have heart failure, taking SGLT2 inhibitors lowers the overall mortality risk as well as the chance of death from cardiovascular causes. Patients who are at a higher risk of dying as a whole are the ones who have proved to benefit from this. It has been established that SGLT2 inhibitors reduce the risk of cardiovascular mortality as well as the rate of hospitalizations and urgent care visits that are associated with heart failure in a range of different populations.